Supplementary Figure S5 from Obesity Is Associated with Altered Tumor Metabolism in Metastatic Melanoma - Andrew W. Hahn (15024693) (2025)
Immune cell analysis by BMI and sex. A. Immunohistochemistry (IHC) analysis of the MDA cohort stratified by BMI and sex. Line represents median +/- interquartile range; each dot represents a single tumor. B. IHC analysis of the Gide cohort stratified by BMI and sex. Line represents median +/- interquartile range; each dot represents a single tumor.